Peranan Komunikasi Partisipatif Opinion Leader dalam Mendukung Percepatan Vaksinasi Covid-19 - Ardiyansyah Ardiyansyah; Ayu Nurkhayati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The Covid-19 vaccination policy was implemented by the central government in the hope of stopping the spread of the virus related to Covid-19, as was the case with the Jambi City government, but in its implementation there were still many people who had not been vaccinated. Those who choose not to be vaccinated do so for various reasons, especially concerns about the contents and safety of the Covid-19 vaccine for their bodies. Vaccines are one of the most important solutions in warding off the Covid-19 virus, so socialization must be continuously carried out through various efforts, including the involvement of opinion leaders to approach and understand the community through the role of participatory communication. The purpose of this study was to determine the role of participatory communication from opinion leaders in supporting the acceleration of Covid-19 vaccination in the Lebak Bandung Village, Jambi City. This research departs from the theory of participatory communication, and the type of research used is field research with a descriptive qualitative approach. There were 5 informants in the study, the data collection techniques used were observation, interviews and documentation. The results of this study indicate that the role of participatory communication Opinion leaders in supporting the co-19 vaccination policy program is carried out through several stages, namely; First, understand the target audience for communication by empathizing and appreciating the audience's attitude towards vaccines. Second, managing or compiling messages about the covid-19 vaccine in language that is easy to understand while still guided by government information or appeals. When, the stages of the communication process are carried out persuasively and interactively. Fourth, choose communication channels and media according to their function in the public.